2014
DOI: 10.1182/blood-2014-01-551234
|View full text |Cite
|
Sign up to set email alerts
|

PIM inhibitors target CD25-positive AML cells through concomitant suppression of STAT5 activation and degradation of MYC oncogene

Abstract: Key Points• CD25 is a predictive biomarker for sensitivity to PIM inhibitors in AML cells.• PIM inhibitors may prolong overall/relapse-free survival through attenuating STAT5 activation and destabilizing MYC in CD25 1 AML cells.Postchemotherapy relapse presents a major unmet medical need in acute myeloid leukemia (AML), where treatment options are limited. CD25 is a leukemic stem cell marker and a conspicuous prognostic marker for overall/relapse-free survival in AML. Rare occurrence of genetic alterations amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
4
26
0
5
Order By: Relevance
“…As expected from cell culture experiments, mice treated with AZD1208 had activated STAT signaling; this activation was significantly inhibited in mice with combination treatment. Following treatment with AZD1208, induction of PIM1 protein levels was increased, as previously reported with other PIM inhibitors [58]. These results support dual inhibitor treatment for a specific subset of T-ALL tumors expressing PIM1.…”
Section: Resultssupporting
confidence: 86%
“…As expected from cell culture experiments, mice treated with AZD1208 had activated STAT signaling; this activation was significantly inhibited in mice with combination treatment. Following treatment with AZD1208, induction of PIM1 protein levels was increased, as previously reported with other PIM inhibitors [58]. These results support dual inhibitor treatment for a specific subset of T-ALL tumors expressing PIM1.…”
Section: Resultssupporting
confidence: 86%
“…PIM inhibitors have been investigated in AML cells as single agents as well as in combination, with varying potencies and cellular consequences[5,7,10,14,17,31,3344]. Downstream mTOR targets (4E-BP1, PRAS40, eIF4B)[23,45,46] and upstream regulators (TSC2) [47] have been identified as Pim targets, and our RPPA investigations support the reports of Pim activity on mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Pim-1 kinase also regulates MET receptor tyrosine kinase levels and signaling via translation through phosphorylation of eIF4B[6]. More recently, Pim inhibition has been demonstrated to suppress STAT5 activation and reduce MYC protein half-life in higher CD25-expressing subpopulations of AML cell lines[7]. Thus, inhibition of Pim kinases may be an avenue to target AML cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies carried out in AML patients have shown that patients with a higher percentage of CD25-positive AML blasts have poor overall survival or relapse-free survival [126,127]. The enhanced CD25 expression in AMLs seems to be induced by STAT5 and MYC hyperactivation occurring in many AMLs: both STAT5 and MYC play a key role in leukemia-initiating activity [128,129].…”
Section: Cd25 and Cd32mentioning
confidence: 96%